Volume 2A: 33rd Computers and Information in Engineering Conference 2013
DOI: 10.1115/detc2013-13155
|View full text |Cite
|
Sign up to set email alerts
|

A Privacy Preserving Data Mining Methodology for Dynamically Predicting Emerging Human Threats

Abstract: This paper proposes a privacy preserving data mining driven methodology for predicting emerging human threats in a public space by capturing large scale, real time body movement data (spatial data represented in X, Y, Z coordinate space) using Red-Green-Blue (RGB) image, infrared depth and skeletal image sensing technology. Unlike traditional passive surveillance systems (e.g., CCTV video surveillance systems), multimodal surveillance technologies have the ability to capture multiple data streams in a real tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In other works, cues such as inferring respiratory rates (by the rising and falling of the chest) and detecting fidgeting (by detecting rapid oscillations of a person's knee), have been explored (Burba, Bolas, Krum, & Suma, 2012). Manohar and Tucker utilized skeletal joint data to predict the emergence of human threats in an audience (Manohar & Tucker, 2013). Such techniques illustrate the potential of machine learning methods using skeletal data.…”
Section: Modeling Body Poses Using Skeletal Joint Datamentioning
confidence: 98%
“…In other works, cues such as inferring respiratory rates (by the rising and falling of the chest) and detecting fidgeting (by detecting rapid oscillations of a person's knee), have been explored (Burba, Bolas, Krum, & Suma, 2012). Manohar and Tucker utilized skeletal joint data to predict the emergence of human threats in an audience (Manohar & Tucker, 2013). Such techniques illustrate the potential of machine learning methods using skeletal data.…”
Section: Modeling Body Poses Using Skeletal Joint Datamentioning
confidence: 98%
“…If the predictive accuracy of the data mining model falls below this predictive accuracy, then the new patient gait data will be included in the training data, with the model retrained using the same steps originally used during model generation. Manohar and Tucker have demonstrated the feasibility of using non-wearable sensors for modelling human body movement data in order to accurately perform emerging threat detection [34]. Behoora and Tucker have discovered correlations between engineering designers’ body language and their emotional states [35,36].…”
Section: Methodsmentioning
confidence: 99%
“…As new incoming patient data is acquired, the models generated by the data mining algorithms employed in this work can be iteratively updated, once their predictive accuracies fall below a given threshold (determined by the healthcare decision makers). Using non-invasive sensors, the authors have demonstrated the feasibility of modeling body movement data in this manner to predict emerging human behavior patterns (for security applications) and emotional states (for engineering education applications) with relatively high accuracy (Manohar and Tucker 2013; Behoora and Tucker 2014; Behoora and Tucker 2015). The authors have also demonstrated that these non-invasive sensors are capable of modeling and predicting medication adherence in patients with neurologically induced movement disorders (C.…”
Section: Methodsmentioning
confidence: 99%